2021
DOI: 10.3389/fmed.2021.659108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dynamic Hyperinflation on Left Ventricular Diastolic Function in Healthy Subjects — A Randomized Controlled Crossover Trial

Abstract: Objective: Diastolic dysfunction of the left ventricle is common in patients with chronic obstructive pulmonary disease (COPD). Dynamic hyperinflation has been suggested as a key determinant of reduced diastolic function in COPD. We aimed to investigate the effects of induced dynamic hyperinflation on left ventricular diastolic function in healthy subjects to exclude other confounding mechanisms associated with COPD.Design: In this randomized controlled crossover trial (NCT03500822, https://www.clinicaltrials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“… 30 It is also recognized that patients with heart failure, either with preserved 31 or reduced 32 ejection fraction who have comorbid COPD have worse functional class than those without lung disease. 33 Hyperinflation has again been implicated in this as it has been associated with more left ventricular diastolic impairment and reduced performance on the six-minute walk test (6MWT). Reduction of hyperinflation with rigorous bronchodilator therapy is also reported to increase end diastolic volumes.…”
Section: Causes Of Impairment In Copdmentioning
confidence: 99%
“… 30 It is also recognized that patients with heart failure, either with preserved 31 or reduced 32 ejection fraction who have comorbid COPD have worse functional class than those without lung disease. 33 Hyperinflation has again been implicated in this as it has been associated with more left ventricular diastolic impairment and reduced performance on the six-minute walk test (6MWT). Reduction of hyperinflation with rigorous bronchodilator therapy is also reported to increase end diastolic volumes.…”
Section: Causes Of Impairment In Copdmentioning
confidence: 99%
“…At high levels of inflation and in hearts with greater volume, increased septal flattening suggests that left ventricular underfilling during hyperinflation may be primarily a result of ventricular interaction exacerbated by ventricular interdependence ( Robotham et al, 1983 ). In a randomized controlled trial conducted by Urban et al (2021) , it was demonstrated that dynamic pulmonary hyperinflation has a notable impact on left heart diastolic function, expressed as the E/A ratio in echocardiography, and leads to an increase in ventricular filling pressures, as indicated by the E/e' ratio. They highlighted an inverse correlation between positive end expiratory pressure and E/A ratio.…”
Section: Introductionmentioning
confidence: 99%